Modelling and control of cable-driven robots - Seyed Masood Dehghan Banadaki (2008)
This thesis concerns the study of the modeling and control of cable-driven robots. A Cable-Driven Robot (CDR) is formed by replacing all the supporting legs of a parallel robot with cables. In comparison with the conventional serial and parallel robots, CDRs have the advantages of simple mechanical structure, large workspace, low moment inertia, and high speed motion. One distinctive characteristic of cabledriven robots is the unilateral property of the cables, i.e. they can only pull but not push. In this thesis, the forward and inverse kinematics, velocity and acceleration analysis, tension analysis, dynamic modeling and control of the cable-driven robot are investigated. The forward kinematics of a CDR is difficult because of its closedloop structures, while the inverse kinematics is relatively simple as it can be decoupled into individual cables. The Newton-Raphson method is adopted to solve the forward displacement numerically. Static and dynamic analysis for a cable-driven robots are also studied. A complete dynamic model of a CDR, including the end-effector dynamic model and actuator dynamic model has been derived. By combining these equations, the overall dynamic model of the system is obtained. Moreover, two approaches for the control of cable-driven robots has been pointed out, namely independent joint control approach and computed torque approach. The first method uses local independent PID controllers at each joint to control the position of the end-effector, while the second one is based on the control law development using computed torque method. Finally, a planar cable-driven robot prototype has been build to investigate the control performance of CDRs. The conclusions of the present study and future research are also outlined in the thesis.